Exploring the Experiences of Early Married Young Madi Girls. Case Study: Madi Sub Region (Moyo District) - Jovia Dranzoa (Uganda Christian University, 2024)
This study report was undertaken to explore the experiences of early married young madi girls. It was guided by two objectives; to identity Factors related with early marriage in Madi, to explore the experiences of the married young Madi girls. The investigator used a sample scope of 63 respondents and used questionnaires and interview guide to gather data and later the data was examined using the statistical package for social sciences (SPSS). Outcomes of the primary objective showed that factors associated with early marriage in Madi have a significant effect on early marriage. Reinforced by the responses; 62% were positive to the statement that limited access to comprehensive sexuality education and reproductive health information can further spread early marriage; 61% respondents were confident to the declaration that limited educational opportunities and unemployment contribute to the perpetuation of early marriage. On the other hand, 75% instituting the mainstream were disagreeing to the declaration that parental and community expectations and pressures based on cultural and religious beliefs can strongly influence early marriage decisions among young individuals. Results of the second objective revealed that experiences have a significant effect on the married young Madi girls; 62% forming the majority of respondents were positive to the statement that married young girls are often subjected to physical and sexual violence, which exacerbates mental health issues like depression and anxiety, 51% had a positive response to the statement that married girls frequently face pressures to conform to traditional gender roles, which can stifle personal aspirations and reinforce subservient positions within the household, 75% were positive to the statement that early marriages are often associated with an increased risk of complications during pregnancy and childbirth, such as premature births, little birth weight infants, and maternal death. The government should educate communities about the negative consequences of early marriage on health, education, and economic opportunities. Promote the benefits of keeping girls in school. Strengthen laws that set the minimum age for marriage at 18 and ensure these laws are enforced. Provide legal support and protection for girls at risk of early marriage.
Undergraduate research